Comparison of lower limb isokinetic muscle performance between road cyclists and middle distance runners - Rannama, I.; Baskin, K.; Roosalu, M.; Port, K.; Kunitson, V. (LASE Journal of Sport Science, 2013)
The purpose of this study was to compare the isokinetic muscle performance of lower limbs in middle distance runners and road cyclists. Subjects: 10 competitive Estonian middle distance runners (age 23.8 ± 3.8 yrs., height 181.8 ± 2.8 cm, mass 73.6 ± 7.4kg ) and 16 road cyclists (21.1 ± 3.5 yrs., 181.5 ± 5.0cm, 74.8 ± 7.0kg) volunteered in this study. Methods: Isokinetic strength of ankle plantar flexors (A-pf), ankle dorsal flexors (A-df), knee (K) and hip (H) extensors (ex) and flexors (fl) were measured with Humac NORM isokinetic dynamometer in angular speeds 60, 180 and 240 °/s. Isokinetic peak torque (PT), and power (P) values of best repetition and total work (ToW) of 15 repetitions in angular speed 240°/s were expressed as a mean of dominant and non-dominant leg. The absolute and relative isokinetic values were compared between runners and cyclists. Results: The comparison of PT values shows that cyclists have significantly (p<0.05) higher results in A-pf and K-fl in all testing speeds. No significant differences between A-df, K-ex, H-fl and H-ex PT values at any speed were found. Cyclists had also significantly higher P results in A-pf, K-fl and K-ex in all testing speeds and tendency (p=0.08) in H-ex 60°/s. ToW values of A-pf, K-ex and K-fl were significantly higher in cyclists group, but runners had higher values in H-fl. Conclusion: Cyclists have higher isokinetic muscle performance values in A-pf, K-fl, and K-ex and runners have higher total work ability in H-fl. No significant differences in A-df and H-ex performance between cyclists and runners were found. Runners and cyclists have also different power-velocity curves of A-df, H-ex, K-ex and K-fl